PENGEMBANGAN MEDIA KOTAK CITA-CITA PORTABEL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SD - Harahap, Rizka Khoirina; Faisal, F (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to determine the validity, practicality, and effectiveness of developing dream box media to increase learning motivation for class III of PAB 23 Patumbak Private Elementary School. This research is to provide a solution for students, namely that there are still many who do not focus on learning, they spend more time on unproductive things, this is due to the lack of motivation from teachers.  The provision of motivation carried out by teachers is still not able to arouse students' enthusiasm for learning so that teaching and learning activities do not run as expected, efforts to clarify learning objectives and efforts to create a pleasant learning atmosphere are still not optimal, this is due to the limited capabilities and costs of teachers. This research is research and development (Research and Development) using the ADDIE Analysis, Design (Planning), Development (Development), Implementation (Implementation), and Evaluation (Evaluation) development model. The subjects in this research were students and teachers of class III of PAB 23 Patumbak Private Elementary School. Based on the research results obtained, media content expert validation in stage I obtained a score of 68.33% in the "decent" category, for media content expert validation in stage II obtained a score of 90.21% in the "very feasible" category. Based on the media design expert's validation in stage I, they obtained a score of 67.91% "within the "decent" category, for validation the media design expert in stage II obtained a score of 75.83% in the "decent" category. From the results of the practicality test, the teacher's response received a score of 90% in the "very practical" category and the results of the practicality test of student responses obtained a score of 75.67% in the "practical" category. The results of the analysis of the effectiveness of the questionnaire to increase learning motivation obtained a score of 91.38% "very effective", and for the questions results obtained a score of 64.17% in the "effective" category. It is known that the effectiveness of the portable dream box game has a positive impact and can be used as a motivational tool to increase students' enthusiasm for achieving their goals.